2019
DOI: 10.1111/camh.12323
|View full text |Cite
|
Sign up to set email alerts
|

Family functioning moderates the impact of depression treatment on adolescents’ suicidal ideations

Abstract: Purpose The purpose of this study was to explore whether adolescent‐perceived family functioning moderates the depression treatment effects on suicidal ideations. Methods This is a nonpreregistered exploratory secondary analysis of the TADS RCT, which included four treatment groups: fluoxetine, CBT, their combination, and placebo. A random coefficients regression model with posteriori CONTRAST statements was conducted to examine the effects of depression treatment on adolescents’ suicidal ideations over time (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 53 publications
2
14
0
2
Order By: Relevance
“…Families can establish appropriate communication with their children regarding mental health conditions and help them in building their individual resilience and proper coping skills (Beardslee, Chien & Bell 2011 :248). In addition, supportive environments constitute a reliable support system for mitigating depressive symptoms amongst adolescents (Dardas 2019 :251). Roohafza et al ( 2014 :947) posited that perceived support systems, especially positive re-interpretation, are crucial in recovery of adolescents from depression.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Families can establish appropriate communication with their children regarding mental health conditions and help them in building their individual resilience and proper coping skills (Beardslee, Chien & Bell 2011 :248). In addition, supportive environments constitute a reliable support system for mitigating depressive symptoms amongst adolescents (Dardas 2019 :251). Roohafza et al ( 2014 :947) posited that perceived support systems, especially positive re-interpretation, are crucial in recovery of adolescents from depression.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The moderation model suggested by Baron and Kenny and Kraemer and colleagues was utilized for analyses [13,14]. In these models, a moderator is an independent variable that impacts the strength or direction of associations between an independent variable and the dependent variable [15]. Thus, we analyzed three associations to test the moderating effect of age on the relationship between depression and sleep.…”
Section: Analysis Strategiesmentioning
confidence: 99%
“…Therefore, society must pay more attention to the Chinese adolescent suicidal ideation problem [ 8 , 13 ]. Existing studies have revealed that risk factors such as an unsupportive family environment [ 2 ], drug abuse [ 14 ], and bullying may affect the suicidal ideation of adolescents, of which an unsupportive family environment plays a crucial role in its formation [ 15 , 16 ]. Low [ 17 ] revealed that a negative parenting style often leads to a higher risk of suicide in adolescents.…”
Section: Introductionmentioning
confidence: 99%